On the grammaticalization of inferential evidential meaning: English "seem" and German "scheinen" - Whitt, Richard J. (University of California, Berkeley, 2015)
This paper provides an account of inferential evidential meaning in English and German, realized by seem and scheinen, respectively. The focus is on the grammaticalization of these verbs into semi-auxiliaries that take infinitive complements, a process localized mainly to the seventeenth and eighteenth centuries by the current study. Uses involving complement clauses and parentheticals are also investigated. A number of diachronic corpora are consulted for data, thus painting a clearer picture of the timing of this grammaticalization scenario. Results are discussed briefly in a cross-linguistic perspective.